Removing the skipping effect from music record - Sim, Ghim Hong. (2010)
Over the years, technology and tastes have changed greatly to the point where it seems that most music lovers have changed from record to CD. The skipping effect in music record has been one of the issues. Scratches on the record can be removed manually using the physical method. However, this is a very time consuming and costly method. If it can be removed using a computing platform with just one single click, removal of skips will become an easy task. Vinyl record lovers may still prefer the authentic sound quality of the music if the skips issue can be resolved. By modeling the entire scratched record as a sum of band-limited signal with additive shot-noise, we can simply view the scratches (skipping effect) as Dirac's. Thus, as long as we are able to remove the shot-noises from the total signal, we will be able to obtain the band-limited signal (the perfect record without the skipping effect). Using the concept of Finite Rate of Innovations, together with the appropriate sampling kernel and reconstruction method, the innovative part of a signal (e.g., time instants and weights of Diracs) can thus be indentified and removed. Once the Diracs can be removed, it means that the skipping effect from the music record can also be removed.